Peningkatan Kualitas SDM Pengelola Desa dalam Digitalisasi Desa Wisata - Rosiana, Eka Nuraisah; Maulina, Lien; Irani, Siti Yulia; Daniati, Hanna; Kuswandi, Dede (Stupa, 2023)
This study aims to determine the quality of human resources, digitalization of tourist villages, and strategies to improve the quality of human resources in digitalization efforts in the Cikakak Tourism Village. The research was conducted using a qualitative research method, with data collection using structured interviews with the village government, BUMDes, Pokdarwis, Pokja, and tourism managers. The results of this study show that the quality of human resources managing the Cikakak Tourism Village in terms of physical capabilities in the form of health human resources, both village government, BUMDes, Pokdarwis, Pokja, and tourism managers, is quite good. Then to digitize the Cikakak Tourism Village, it utilizes several digital platforms, namely websites, Instagram, and YouTube. However, the use of digital platforms, including websites, Instagram, and YouTube, still has deficiencies in helping tourists buy entrance tickets to tourist attractions, order homestays, culinary delights, and tour packages online. The Cikakak Tourism Village has low quality human resources in digitalization efforts, this can be seen in terms of the number of digital media managers who are still small, the knowledge and ability of human resources in digitizing tourist villages is also still low.